2016
DOI: 10.5194/cp-12-1029-2016
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and ecosystems dynamics over the last 6000 years in the Middle Atlas, Morocco

Abstract: Abstract. The present study aims at reconstructing past climate changes and their environmental impacts on plant ecosystems during the last 6000 years in the Middle Atlas, Morocco. Mean January temperature (T jan ), annual precipitation (P ann ), winter (P w ) and summer (P s ) precipitation, and a seasonal index (SI) have all been quantified from a fossil pollen record. Several bio-and geo-chemical elements have also been analysed to evaluate the links between past climate, landscape, and ecosystem changes.Ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…2b). High-resolution speleothem data from southern Iberia show Mediterranean climate conditions in southern Iberia between 4800 and 3000 cal BP (Walczak et al, 2015) for the Alboran Sea during the late Holocene is consistent with a climate reconstruction available from the Middle Atlas (Morocco), which show a trend over the last years towards arid conditions as well as higher precipitation seasonality between 4000 and 2000 cal yrs BP (Nourelbait et al, 2016). There is also good evidence from many records to support late Holocene aridification in southern Iberia.…”
Section: Late Holocene (4000 To 2000 Cal Yrs Bp)supporting
confidence: 78%
See 1 more Smart Citation
“…2b). High-resolution speleothem data from southern Iberia show Mediterranean climate conditions in southern Iberia between 4800 and 3000 cal BP (Walczak et al, 2015) for the Alboran Sea during the late Holocene is consistent with a climate reconstruction available from the Middle Atlas (Morocco), which show a trend over the last years towards arid conditions as well as higher precipitation seasonality between 4000 and 2000 cal yrs BP (Nourelbait et al, 2016). There is also good evidence from many records to support late Holocene aridification in southern Iberia.…”
Section: Late Holocene (4000 To 2000 Cal Yrs Bp)supporting
confidence: 78%
“…Very few large-scale climate reconstruction of precipitation exist for the whole Holocene (Bartlein et al, 2011;Mauri et al, 2014;Guiot andKaniewski, 2015, Tarroso et al, 2016) and, even at local scales, pollen-inferred reconstructions of seasonal precipitation are very rare (Wu et al, 2007;Peyron et al, 2011Peyron et al, , 2013Combourieu-Nebout et al, 2013, Nourelbait et al, 2016.…”
Section: A North-south Precipitation Pattern?mentioning
confidence: 99%
“…This pattern was reversed at around 4500 cal yr BP (Magny et al, 2013). Quantitative pollenbased precipitation reconstructions from sites in northern Italy indicate humid winters and dry summers during the early to mid-Holocene, whereas southern Italy was characterized by humid winters and summers; the N-S pattern reverses in the late Holocene, with drier conditions at southern sites and wet conditions at northern sites (Peyron et al, 2011(Peyron et al, , 2013. These findings support a north-south partition for the central Mediterranean with regards to precipitation, and they also confirm that precipitation seasonality is a key parameter in the evolution of Mediterranean climates.…”
Section: Introductionmentioning
confidence: 93%
“…Recent studies have contributed further knowledge regarding patterns and processes of Holocene vegetation change in the northwestern Middle Atlas at Ras el Ma and Dayat Hachlaf (Nourelbait et al, 2014(Nourelbait et al, , 2016Tabel et al, 2016), and forthcoming data for the Holocene are indicated for Lake Tifounassine (Cheddadi et al, 2015). At Dayat Hachlaf, forested conditions with Quercus (undifferentiated) and Pinus are recorded throughout the record from 6,000 cal yr BP, and include a shift in forest composition around 3,500 cal yr BP, with the expansion of Cedrus (Nourelbait et al, 2016). In contrast, the nearby record of Ras el Ma documents a late development of forest with Quercus and Cedrus only after 5,000 cal yr BP (Nourelbait et al, 2014).…”
Section: Background and Rationalementioning
confidence: 99%
“…The biological and bioclimatic diversity of the region, particularly as contained within the Atlas mountain ranges (Ozenda, 1975;Medail and Quezel, 1997), furthermore provides a valuable "test-bed" for understanding the wider response of FIGURE 1 | The study region and location of pollen records, showing: (a) the location of the Middle Atlas (MA), High Atlas (HA) and Rif mountain ranges in Morocco; (b) the western Middle Atlas and the location of the study site and other Holocene pollen studies cited in the text; and (c) length and chronological control of dated pollen records for the Middle Atlas. Key to sites: AFO-Dayat Afourgagh (Lamb et al, 1991); ALI-Lake Sidi Ali (1-Sidi Ali sub-basin, Lamb et al, 1999; 2-Sidi Ali deep lake, this study); CDZ-Col du Zad (Reille, 1976); HAC-Dayet Hachlaff (Nourelbait et al, 2016); HAR-Taguelmam N'Harcha (Lamb et al, 1991); ICH-Ait Ichou (Tabel et al, 2016); IFF-Dayat Iffir (Lamb et al, 1991); IFR-Dayat Ifrah (Rhoujjati et al, 2010;Reddad et al, 2013); RAS-Ras el Ma (Nourelbait et al, 2014); TIF-Tifounassine (Cheddadi et al, 2015); TIG-Tigalmamine (Lamb et al, 1989Lamb and van der Kaars, 1995;Cheddadi et al, 1998).…”
Section: Background and Rationalementioning
confidence: 99%